Calculating water column height in the aboveground part of a low-altitude tank at abnormally low ambient temperatures - Neufeld Elena; Asmankin Evgeny; Ushakov Yuriy; Ivanov Pavel; Kargaev Ivan (E3S Web of Conferences, 2023)
The relevance of the study is confirmed by the widespread use of water tanks in rural settlements and farms in which ice forms inside the tank at abnormally low ambient temperatures, leading to a failure in the water supply system. The mathematical model is based on the heat balance equation, which takes into account the heat exchange of water with the ground and air through the separating metal wall, as well as heat transfer from water to air under the tank roof. Taking into account the low-potential energy of the ground, the paper presents a method for calculating the temperature of water in a non-height type tank of a given volume and radius. It allows to select the minimum height of its underground part to ensure uninterrupted water supply at average statistical values of ambient temperature and wind speed, registered in the region of research. The functions of the tank underground and above-ground part’s heights from the argument of its total volume to prevent the appearance of ice on the inner surface of the tank are graphically illustrated. The possibility of applying the method to determine the maximum water level in the above-ground part when the period of zero consumption is passed is indicated.